Analysis of Content, Social Networks, and Sentiment of Front-of-Pack Nutrition Labeling in the European Union on Twitter - Septia Irawan, Anggi; Shahin, Balqees; Wangeshi Njuguna, Diana; Nellamkuzhi, Noel Johny; Thiện, Bùi Quốc; Mahrouseh, Nour; Varga, Orsolya (Frontiers in Nutrition, 2022)
In recent years, a concerted political effort has been made at national and EU level to promote the consumption of healthy foods. The European Commission (EC) expressed a need for a harmonized, mandatory front-of-pack nutrition labelling (FOPL) system at EU level. The EC intends to adopt the proposal by the end of 2022. Our research work seeks to understand the public discourse on FOPL in the EU through Twitter, by content analysis of tweets, sentiment analysis and mapping network characteristics. Search and data collection of tweets were carried out by using Twitter Application programming interface (API) without time or language limit. The content was coded using the QRS Nvivo software package and analysed by themes. Automatic sentiment analysis was carried out by QSR Nvivo, network analysis by Gephi 0.9.2. 4073 tweets were posted, mainly from the United Kingdom, Spain and France. The emerging themes from Twitter discussions include food labelling types, food industry, healthy food vs. unhealthy food in the context of food labelling, EU regulation, political conflict, and science and education. Nutri-Score dominated the Twitter discussions. The general topic is perceived negatively by Twitter users, with more positive sentiments towards the food industry, while negative sentiments towards discourses on political conflicts were observed. The network analysis showed centralized communication which was hardly present between countries. Our results have made it clear that FOPL discussions on Twitter are limited to a very narrow group of people, it seems necessary to inform a wide range of consumers about existing and upcoming FOPL schemes. Education programs should empower consumers to understand what healthy eating is and how it relates to FOPL, irrespective of the labelling system that is implemented.